Do not let perfect be the enemy of good: the current reality of Bordetella testing - Rebecca Yee (Microbiology Spectrum)
ABSTRACT Diagnosis of Bordetella pertussis is made by using polymerase chain reaction (PCR) to detect insertion sequence 481 (IS481). However, IS481 is found in both B. pertussis and Bordetella holmesii. In a recent study, Cole et al. (Microbiol Spectr 12:e00783-24. https://doi.org/10.1128/spectrum.00783-24) compared the accuracy of assays performed at two different commercial laboratories that used IS481 as a molecular target against a multiplex PCR assay performed at the Centers for Disease Control and Prevention (CDC) that can differentiate the different Bordetella species. The results demonstrated that the overall agreement among the assays from the commercial laboratories and the CDC was 85%. Only a small percentage (1.4%) of specimens positive for IS481 were identified as B. holmesii. This study suggests that PCR tests using IS481 as a target provide reliable diagnosis for pertussis. However, end users should recognize the limitations of PCR testing for pertussis including the inability to differentiate and monitor transmission of non-pertussis Bordetella species.